Passive Mixer and Separator Integrated on a Ceramic-Based Microfluidic Device - Seon, Ji-Yun; Joon Yoon, Young; Tae Kim, Hyo; Kim, Chang-Yeoul; Kim, Jong-Hee; Koo Baik, Hong (Asian Journal of Chemistry, 2013)
A ceramic-based microfluidic device including a passive mixer and a passive separator was fabricated via a conventional low temperature co-fired ceramic process and photolithographic technique. In the mixing process, the configuration of a conventional diffusion-type passive mixer with a 500 μm channel width and 50 μm height was used. The total length of the mixing channel was 15.8 cm. The maximum mixing efficiency of the diffusion-type passive mixer was 97.3 % at a flow rate of 0.3 μL/min. In the separation process, six branch channels were arranged at the end of the pinched segment for separating different sized particles from one another. The findings confirmed that microbeads for a target channel were separated efficiently by controlling the hydrodynamic conditions of the microfluids.